Clinical evolution of ST11 carbapenem resistant and hypervirulent Klebsiella pneumoniae - Miaomiao Xie (Nature Portfolio, 2021)
Carbapenem-resistant and hypervirulent Klebsiella pneumoniae strains are emerging. Here Xie et al. show that these phenotypes are carried on a plasmid formed from the fusion of a virulence plasmid with a conjugative plasmid.